Risk factors of adverse events in endoscopic retrograde cholangiopancreatography for patients aged ≥85 years. Issue 7 (24th March 2018) - Takahashi, Koji; Tsuyuguchi, Toshio; Sugiyama, Harutoshi; Kumagai, Junichiro; Nakamura, Masato; Iino, Yotaro; Shingyoji, Ayako; Yamato, Mutsumi; Ohyama, Hiroshi; Kusakabe, Yuko; Yasui, Shin; Mikata, Rintaro; et al.
Abstract : Aim: Little is known about the factors that contribute to the occurrence of adverse events in endoscopic retrograde cholangiopancreatography (ERCP) for people aged ≥85 years and safety for the super‐old. Therefore, we decided to identify these factors and to examine whether ERCP is safe in the super‐old. Methods: This was a single‐center retrospective study. A total of 137 patients aged ≥85 years who underwent therapeutic ERCP at Chiba University Hospital from January 2012 to March 2017 were retrospectively reviewed. Results: Four cases of Billroth II reconstruction and two cases of gastrectomy with Roux‐en‐Y reconstruction were excluded, and 131cases in total were examined in the present study. A total of 10 and 121 cases with and without adverse events, respectively, were present. Using univariate analysis, factors significantly contributing to the occurrence of adverse events in therapeutic ERCP were identified as aged ≥90 years ( P  = 0.0096), duodenal papilla cancer ( P  = 0.0012), gallbladder carcinoma ( P  = 0.023), and biliary metal stenting ( P  = 0.040). In multivariate analysis, only ≥90 years‐of‐age was a significant factor ( P  = 0.049). In addition, comparison between 25 cases of the super‐old and 106 cases aged 85–89 years was carried out. In the super‐old group, the average value of the American Society of Anesthesiologists physical status classification and Charlson's Comorbidity Index were significantly better than those in 85–89‐year‐olds ( P  = 0.0035 and P  < 0.0001, respectively). Conclusions: Although the super‐old group had fewer comorbid diseases, they had significantly increased adverse events compared with patients aged 85–89 years.Geriatr Gerontol Int 2018; 18: 1038–1045 .